Sikap Perilaku Keseharian Masyarakat dan Lingkungan Keluarga Sebagai Cermin Keberhasilan Citizenship Education - Juliati Juliati; Muhammad Firman (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
In globalization era today we as world member can feel the spread of science andtechnology advance in which one country with another country will know each otherstrength and weakness through evaluation of its various technology and communicationwhich influence people in various countries. From year to year there are many people whoare increasingly go to jail. Whereas the failure and success of citizen education can be seenfrom daily attitude and behavior of community and their family environment. So, it is notsurprising that there are more and more prisoners from year to year. This indicate thatmany citizens who are involved in infringement which result in criminality. The solutionis that citizen education material should be prepared to suit with situation from influenceof science and technology advance, in addition the government should control communityand their family environment to be better (good citizenship). The material and the wayteacher teach (method, media and model) should be arranged. As suggested by William T.Callahan (1990: 338) that good citizenship was not born, but is in interpersonal, intellectualabilities which are needed and should be learned seriously, then applied to community andtheir family environment as citizen of people in various countries. DOI: 10.15408/sjsbs.v3i3.7865